2023
DOI: 10.1186/s12979-023-00369-1
|View full text |Cite
|
Sign up to set email alerts
|

Systemic immune response in young and elderly patients after traumatic brain injury

Marta Magatti,
Francesca Pischiutta,
Fabrizio Ortolano
et al.

Abstract: Background Traumatic brain injury (TBI) is a leading cause of death and long-term disability worldwide. In addition to primary brain damage, systemic immune alterations occur, with evidence for dysregulated immune responses in aggravating TBI outcome and complications. However, immune dysfunction following TBI has been only partially understood, especially in the elderly who represent a substantial proportion of TBI patients and worst outcome. Therefore, we aimed to conduct an in-depth immunolo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 83 publications
1
5
0
Order By: Relevance
“…Overall, we show that studying acute patterns of plasma protein expression can help quantify focal injury and identify potential processes, including neurodegeneration and inflammation, that are important in human TBI pathophysiology. This provides a basis for more rational classification of TBI based on pathophysiology, We found acutely raised levels of inflammatory proteins IL6, IL10, IL1b, IL8, IL15, IL16, serum amyloid A (SAA1) and CCL2 after TBI, in line with prior studies 20,21,3034,2229 . In contrast to many prior studies, we recruited a non-TBI trauma control cohort, and thus demonstrate that changes in plasma levels of IL8, SAA1 and IL15 may actually reflect a general injury response.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Overall, we show that studying acute patterns of plasma protein expression can help quantify focal injury and identify potential processes, including neurodegeneration and inflammation, that are important in human TBI pathophysiology. This provides a basis for more rational classification of TBI based on pathophysiology, We found acutely raised levels of inflammatory proteins IL6, IL10, IL1b, IL8, IL15, IL16, serum amyloid A (SAA1) and CCL2 after TBI, in line with prior studies 20,21,3034,2229 . In contrast to many prior studies, we recruited a non-TBI trauma control cohort, and thus demonstrate that changes in plasma levels of IL8, SAA1 and IL15 may actually reflect a general injury response.…”
Section: Discussionsupporting
confidence: 89%
“…IL16 is produced by CD4+ and CD8+ cells, including microglia in the brain, and acts as a chemokine and activating signal for cells expressing the CD4 receptor, such as Tlymphocytes, monocytes and macrophages [37][38][39] . Peripheral CD4+ T-lymphocyte activation is reported in acute human TBI 21 , while experimental studies have found that CD4+ T-lymphocytes can increase injury severity 40 . Increased IL16 expression is seen in experimental neuroinflammation, as a result of infiltrating immune cells and microglial activation 41 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that sepsis-associated apoptosis of CD8+ T cells leads to lymphopenia and immunosuppression as well as increased susceptibility to secondary infections, in late-stage sepsis patients ( 32 ). A recent study by Magatti et al ( 33 ) found that TBI affected the differentiation ability of CD8 T cells in PBMCs, which are induced to differentiate into low cytotoxicity subtypes, such as memory-precursor effector CD8 T cells, leading to additional challenges, especially in the case of infections. Altogether, these results indicate that several immune cells, especially CD8 T cells, neutrophils, and macrophages, are involved in MASP-1-mediated trauma and sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, few studies have examined circulating biomarker changes in geriatric or pediatric TBI models. This is particularly noteworthy considering that the elderly population registers the highest frequency of TBI-related hospital admissions (135) and have significantly poorer outcomes compared to young patients with similar injury severity (136). This pattern is mirrored in aged TBI mice (137).…”
Section: Knowledge Gaps Limitations and Conclusionmentioning
confidence: 99%
“…This pattern is mirrored in aged TBI mice (137). Notably, blood NfL levels exhibit an age-related increase in TBI patients, hinting at age-linked vulnerability to neuronal damage (136). Determining whether this susceptibility is attributed to age itself or to age-related comorbidities presents challenges in the clinical context.…”
Section: Knowledge Gaps Limitations and Conclusionmentioning
confidence: 99%